Expansion of PD1-positive T Cells in Nodal Marginal Zone Lymphoma: A Potential Diagnostic Pitfall. (May 2020) - Egan, Caoimhe; Laurent, Camille; Alejo, Julie C.; Pileri, Stefano; Campo, Elias; Swerdlow, Steven H.; Piris, Miguel; Chan, Wing C.; Warnke, Roger; Gascoyne, Randy D.; Xi, Liqiang; Raffeld, Mark; et al.
Abstract : The diagnosis of nodal marginal zone lymphoma (NMZL) can be challenging, with the differential diagnosis including other low-grade B-cell lymphomas, reactive hyperplasia, and even some cases of peripheral T-cell lymphoma (PTCL). PTCL may have a perifollicular growth pattern mimicking NMZL. We and others have noted an atypical distribution of T-follicular helper (TFH ) cells in some cases of NMZL. This study was prompted by the diagnosis of NMZL in several cases in which a marked increase of TFH cells, as determined by staining for programmed death-1 (PD1), had prompted suspicion for a diagnosis of PTCL. We analyzed PD1 staining in 48 cases of NMZL to characterize the extent and pattern of the PD1-positive infiltrate. Three main patterns of PD1 staining were identified: follicular pattern (peripheral, n=16; central, n=9; mixed, n=3), diffuse pattern (n=4), and a reduced or normal staining pattern in residual follicles (n=16). A comprehensive analysis of other TFH markers was undertaken in 14 cases with a high content of PD1-positive cells that were confirmed as B-cell lymphoma by clonality analysis. We describe in detail 5 of these cases in which PTCL was an initial consideration. This study illuminates the diverse immunohistochemical patterns encountered in NMZL and highlights a diagnostic pitfall important for diagnostic accuracy.